Pendampingan Pembentukan Karakter Anak Usia Dini Melalui Pembiasaan di RA Adz Dzikra Isyhaarul Jannah Dharmasraya - Sya’adah, Miftahu; Kustati, Martin; Gusmirawati, Gusmirawati; Amelia, Rezki (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The purpose of this community service activity is to shape and build the character of early childhood through habituation so that polite and courteous characters are created at school. This activity focuses on the religious and polite character of children. This community service activity was carried out at RA Adz Dzikra Isyhaarul Jannah Dharmasraya. The mentoring method uses the service learning method which focuses on character formation through habituation through three stages, namely preparation, implementation, and evaluation. This mentoring was carried out on January 2 - March 8, 2024. The results of the community service activity were the formation of character in children because of the habituation carried out every day where children were accustomed to shaking hands and saying hello to teachers and saying sorry and thank you.